The ClinGen Syndromic Disorders Gene Curation Expert Panel: Assessing the clinical validity of 111 gene-disease relationships - Eleanor C. Broeren; Vanessa N. Gitau; Alicia B. Byrne; Pamela Ajuyah; Marie B. Balzotti; Jonathan S. Berg; Krista Bluske; B. Monica Bowen; Matthew P. Brown; Amanda Buchanan; Brendan T. Burns; Nicole J. Burns; et al. (Genetics in Medicine Open)
Purpose: The Clinical Genome Resource (ClinGen) Gene Curation Expert Panels have historically focused on specific organ systems or phenotypes; thus, the ClinGen Syndromic Disorders Gene Curation Expert Panel (SD-GCEP) was formed to address an unmet need. Methods: The SD-GCEP applied ClinGen’s framework to evaluate the clinical validity of genes associated with rare syndromic disorders. A total of 111 gene-disease relationships (GDRs) associated with 100 genes spanning the clinical spectrum of syndromic disorders were curated. Results: From April 2020 through March 2024, 38 precurations were performed on genes with multiple disease relationships and were reviewed to determine if the disorders were part of a spectrum or distinct entities. A total of 14 genes were lumped into a single disease entity, and 24 were split into separate entities, of which 11 were curated by the SD-GCEP. A full review of 111 GDRs for 100 genes followed, with 78 classified as Definitive, 9 as Strong, 15 as Moderate, and 9 as Limited, highlighting cases in which further data are needed. All diseases involved 2 or more organ systems, whereas the majority (88/111 GDRs, 79.2%) had 5 or more organ systems affected. Conclusion: The SD-GCEP addresses a critical gap in gene curation efforts, enabling inclusion of genes for syndromic disorders in clinical testing and contributing to keeping pace with the rapid discovery of new genetic syndromes.